Model of self-organizational dynamics in a semi-deciduous microphyllous forest in eastern Cuba: a restoration approach - Arturo Salmerón López; Gretel Geada López (Revista Cubana de Ciencias Forestales, 2023)
The use of systems modeling as a tool to simulate the dynamics in vegetal communities as responses to disturbances constitutes an alternative for management in protected areas. The objective of this study is to develop a model to simulate the possible self-organizing dynamics in the composition and functional structure of the microphyllous semi-deciduous forest under different disturbance scenarios. Population change equations for dynamogenetic species were determined based on the Leslie matrix, considering functional type and age structure. A conceptual model of the system is defined, that integrates the previous information available on functional composition, structure and interactions. The results of the simulations showed that disturbances occurred in some sectors of the area led the system to equilibrium states very different from the conserved states. The composition, structure, and functional interactions defined in the forest, together with local disturbances, condition the self-organizing dynamics of the system, which can lead to more than one state of equilibrium through different successional trajectories. These aspects facilitate the taking of actions for ecological restoration.